O esforço dos estados na implementação do Sistema Único de Assistência Social : competências e capacidades dos entes subnacionais - Simone de Souza Pegoreti (2019)
The Social Assistance Policy in Brazil has important historic landmarks which corroborated structuring changes in its development which is the Federal Constitution of 1988, in which the Social Assistance was recognized as “Citizenship rights and States’ rights”. Another important regulatory framework is the Organic Law on Social Assistance (LOAS) implemented on December 7 of 1993, which institutes the policy through services, programs, projects and benefits and defines that its management and operationalization must occur in a systemic and integrated way. The regulatory frameworks arising from LOAS, organizes the offerings of this policy by the establishment of the Unified Social Assistance System (SUAS). The implementation of this system has the premise in the federative pact, which is the sine qua non condition of the establishment and implementation of the co-responsibility between the federative entities to establish SUAS. Thus, the goal of this work is to analyze the efforts to implement SUAS in the states sphere considering the relevance of the functions of this entity to corroborate the implementation of SUAS as well as the consolidation of the federative pact on social assistance field. To perform this research we developed a benchmarking instrument called “States effort index in the implementation of SUAS” which was composed of two indices, such as Administrative and functional cooperation and Allocated expense. After, in order to comprehend which are the causal conditions that could explain the effort level variation of the states in the implementation of SUAS, some hypotheses was elaborated in order to affect the effort index. These hypothesis lead to the development of the following independent variables: Legacy of the prior policies; Income social vulnerability; Governor’s party and per capita income of the states- direct taxes plus the mandatory transfers of the Union. The results of this research points out that it is not possible to affirm that the four independent variables, if aggregated, generate causal consequences in relation to the effort of the states in the implementation of SUAS. Nevertheless, the disaggregated analyses of the independent variables compared to dependent variable can contribute to consider some explanations.